1989
DOI: 10.1002/cne.902830413
|View full text |Cite
|
Sign up to set email alerts
|

HRP study of the central components of the trigeminal nerve in the larval sea lamprey: Organization and homology of the primary medullary and spinal nucleus of the trigeminus

Abstract: The medullary and spinal connections of the trigeminal nerve of larval sea lampreys Petromyzon marinus were studied by anterograde and retrograde HRP transport after application into the orbit. Three components were found, all of them ipsilateral: 1) The motor nucleus was undivided in the larva, and its neurons possessed a rich dendritic tree. The single motor root was well separated from the sensory root. 2) The descending root was laterally located, and its fibers ran compactly to spinal levels. 3) Most medu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 60 publications
3
26
1
Order By: Relevance
“…The motoneurons of the cranial nerve nuclei are ChAT-ir in all vertebrates studied so far. The topographical distribution of the somatomotor nuclei innervating the extraocular muscles (III, IV, and VI) in lampreys is well known (Fritzsch and Sonntag, 1988;Fritzsch et al, 1990;Rodicio et al, 1992;Fritzsch and Nothcutt, 1993b;Pombal et al, 1994), as well as the arrangement of the branchiomotor nuclei (Nieuwenhuys, 1972(Nieuwenhuys, , 1977Homma, 1978;Koyama et al, 1987;Anadón et al, 1989;Gonzá lez, 1990;Fritzsch and Northcutt, 1993a). Our immunohistochemical results are consistent with these studies and helped us to ascribe them to their segmental rhombomeric topography (not necessarily coinciding with their segmental origin; see below).…”
Section: Secondary Prosencephalonsupporting
confidence: 91%
“…The motoneurons of the cranial nerve nuclei are ChAT-ir in all vertebrates studied so far. The topographical distribution of the somatomotor nuclei innervating the extraocular muscles (III, IV, and VI) in lampreys is well known (Fritzsch and Sonntag, 1988;Fritzsch et al, 1990;Rodicio et al, 1992;Fritzsch and Nothcutt, 1993b;Pombal et al, 1994), as well as the arrangement of the branchiomotor nuclei (Nieuwenhuys, 1972(Nieuwenhuys, , 1977Homma, 1978;Koyama et al, 1987;Anadón et al, 1989;Gonzá lez, 1990;Fritzsch and Northcutt, 1993a). Our immunohistochemical results are consistent with these studies and helped us to ascribe them to their segmental rhombomeric topography (not necessarily coinciding with their segmental origin; see below).…”
Section: Secondary Prosencephalonsupporting
confidence: 91%
“…These neurons have previously been demonstrated to be cholinergic and nitrergic (Giraldez-Perez et al, 2008). Anatomical and physiological studies indicate that these neurons carry proprioceptive information, from the jaw muscles, tooth pulp, and extraocular muscles, and play an important role in mastication and jaw-closing reflexes through their projections to trigeminal motoneurons (Anadó n et al, 1989;Pombal et al, 1997). The presence of double-labeled neurons suggests that both NO and Ach participate in the integration of these sensorimotor processes.…”
Section: Mesencephalonmentioning
confidence: 95%
“…The time course of retinopetal innervation does not, therefore, parallel that of overall retinal growth. Ultrastructural studies of large larvae have revealed the existence of synaptic contacts between the centrifugal fibres and ganglion cells (De Miguel et al 1989): whether retinopetal innervation and the development of ganglion cells are related needs further investigation.…”
Section: Retinopetal Nuclei Of Larvae and The Development Of Retinal mentioning
confidence: 99%
“…Since the 1970s, the study of the retinopetal system has made considerable progress due to the introduction of neuroanatomical tracer techniques. The presence of retinopetal fibres in both adult and larval lamprey has been confirmed with horseradish peroxidase (HRP) labelling and electron microscopy (Vesselkin et al 1989;De Miguel et al 1989). The central components of this system have been identified in adult lamprey using both retrograde transport (Vesselkin et al , 1984 and electrophysiological techniques (Vesselkin et al 1984).…”
Section: Introductionmentioning
confidence: 97%